Microeconomics - Pindyck, Robert S.; Rubinfeld, Daniel L. (Singapore : Prentice Hall, 2009)
A good grasp of microeconmics is vital for managerial decision making, for designing and understanding public policy, and more generally for appreciating how a modern economy functions.
Introduction : Markets and prices -- Producers, consumers, and competitive markets -- Market structure and competitive strategy -- Information, market failure, and the role of government
Includes index.
Keywords: MICROECONOMICS